Teaching Quantitative Research Method with Three Methods of Learning - Haviz, Muhammad; Maris, Ika Metiza (AT-TA'LIM, 2018)
This study aims to investigated the effect of lecture-discussion (LD), direct instruction (DI)and guide inqury (GI) to students’achievement on quantitative design research. An experimental comparison group post-test only designwas used to prove the hypothesis there is a significant difference of students’achievement on undergraduate biology education class (BEC) and master's economic class (EC)with the using of LD, DI and GI.This study used34 BECs’ student and 26 ECs’ student who take quantitative research courses in the academic year 2016-2017.The students’ achievement was measured by instrument of Research based Learning (RbL). The collected data has been analyzed by using descriptive statistics, and Chi-Square test to determine the comparison in both treatment of classes.The result of this study has shown thatχ2scores of LD(71.276) andχ2scores of DI(203.12) χ2 table α(0.05;0.01) (15.507;20.090). At the using of GI, the quality for students’ achievement scores on BEC is better than EC (standard vs. approaching standard). In conclusion, there was significant difference of students’achievement onBEC and EC with the using of LD, DI and GI.